(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: This study compared the efficacy of prophylactic antibiotics with seven days of conventional antibiotics. Objective: This present study was carried out to evaluate the effectiveness of three doses of prophylaxis with ceftriaxone and metronidazole. Methodology: This parallel arm, randomized control trial was conducted among fifty patients, consisting of 25 cases and 25 controls, with acute appendicitis admitted at Dhaka Medical College Hospital, Popular Medical College Hospital, Dhaka, and Ad-din Barrister Rafique Ul-Haq Hospital, Dhaka, during the period of November 2021 to April 2022. This study was done to evaluate the efficacy of three doses of combined prophylactic antibiotics, ceftriaxone and metronidazole, in acute non-perforated appendicitis cases. The patients in the control group were treated with seven days of conventional antibiotic therapy to compare the efficacy with three doses of prophylactic antibiotics. Results: Among 9 wound infections (15%), 4 patients were in the control group (36.5%), and 5 (40.5%) were in the case group in the study group with combined surgical prophylaxis of ceftriaxone and metronidazole (P=0.001). One patient develops both a wound infection and an intra-abdominal abscess. The study also found that amount to patient (3.3%) with intra-abdominal abscess formation 01 (50%) in control group and 01(50.0%) in combined prophylaxis group (ceftriaxone and metronidazole) (P>0.3). Conclusion: In conclusion no significant difference could be found between the patients who received combined three doses of ceftriaxone and metronidazole and the control groups with regard to age, sex, distribution of symptoms before admission, preoperative temperature, duration of surgery, hospital stay, and concomitant diseases both overall and within each of the three groups of appendiceal examination. Bangladesh Journal of Infectious Diseases, June 2023;10(1):11-15